Image contrast in X-ray reflection interface microscopy comparison of data with model calculations and simulations - Fenter, P (Journal of synchrotron radiation, 2008)
The contrast mechanism for imaging molecular-scale features on solid surfaces is described for X-ray reflection interface microscopy (XRIM) through comparison of experimental images with model calculations and simulated measurements. Images of elementary steps show that image contrast is controlled by changes in the incident angle of the X-ray beam with respect to the sample surface. Systematic changes in the magnitude and sign of image contrast are asymmetric for angular deviations of the sample from the specular reflection condition. No changes in image contrast are observed when defocusing the condenser or objective lenses. These data are explained with model structure-factor calculations that reproduce all of the qualitative features observed in the experimental data. These results provide new insights into the image contrast mechanism, including contrast reversal as a function of incident angle, the sensitivity of image contrast to step direction (i.e. up versus down), and the ability to maximize image contrast at almost any scattering condition defined by the vertical momentum transfer, Q(z). The full surface topography can then, in principle, be recovered by a series of images as a function of incident angle at fixed momentum transfer. Inclusion of relevant experimental details shows that the image contrast magnitude is controlled by the intersection of the reciprocal-space resolution function (i.e. controlled by numerical aperture of the condenser and objective lenses) and the spatially resolved interfacial structure factor of the object being imaged. Together these factors reduce the nominal contrast for a step near the specular reflection condition to a value similar to that observed experimentally. This formalism demonstrates that the XRIM images derive from limited aperture contrast, and explains how non-zero image contrast can be obtained when imaging a pure phase object corresponding to the interfacial topography